THE PERFORMANCE OF THE SERBIAN HOTEL INDUSTRY - Mašić, Saša (The European Journal of Applied Economics, 2013)
The aim of this paper is to determine operating performance of hotel companies in Serbia. The analysis was conducted on a sample that included approximately 31.35% of the total available hotel capacity in Serbia for the period from 2004 to 2011. The sample was designed to be representative of the hotel distribution by territory and category. Business performance of hotel companies was analyzed using TREVPAR and GOPPAR indicators both at the national level, for tourism clusters and the largest Serbian cities. The results show that hotel companies in Serbia, on average, achieved low TREVPAR and GOPPAR values. In 2011, the average TREVPAR of companies in Serbia was 28 EUR, and GOPPAR approximately 3.7 EUR. The study registered a significant decline in the value of these indicators for the period from 2008 to 2011, primarily as a result of the economic crisis. Results significantly better than the national average were achieved by hotel companies from Belgrade that had a mean TREVPAR value of 46.2 EUR and GOPPAR value of 8.6 EUR. During the analyzed period, the largest increase in the value of the analyzed indicators was registered in the city of Kragujevac as a result of significant investments made by the car manufacturer “Fiat” and its sub-contractors. These investments have led to a significant increase in the number of foreign tourist arrivals and consequently to an increase in business performance of hotel companies in Kragujevac.